2020
DOI: 10.1039/d0nr04208k
|View full text |Cite
|
Sign up to set email alerts
|

Using HAADF-STEM for atomic-scale evaluation of incorporation of antibacterial Ag atoms in a β-tricalcium phosphate structure

Abstract: Structural evaluation of ionic additions in calcium phosphates that enhance their performance is a long-lasting area of research in the field of biomedical materials. Ionic incorporation in β-tricalcium phosphate (β-TCP)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…The noticeable diffraction of the generated pattern in terms of d -spacing and crystal planes were matched with the standard ICDD database (card no#: 04-006-9376). No other phase was found in the pattern except rhombohedral β-TCP of R 3 c space group 24 and a similar type of β-TCP has been reported in the literature. 20,25 Rietveld refinement was done to quantify the phase percentage of β-TCP and hydroxyapatite (HA, card no#:01-074-0566) by using Rigaku Smart Lab Studio II software.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The noticeable diffraction of the generated pattern in terms of d -spacing and crystal planes were matched with the standard ICDD database (card no#: 04-006-9376). No other phase was found in the pattern except rhombohedral β-TCP of R 3 c space group 24 and a similar type of β-TCP has been reported in the literature. 20,25 Rietveld refinement was done to quantify the phase percentage of β-TCP and hydroxyapatite (HA, card no#:01-074-0566) by using Rigaku Smart Lab Studio II software.…”
Section: Resultssupporting
confidence: 81%
“…The noticeable diffraction of the generated pattern in terms of d-spacing and crystal planes were matched with the standard ICDD database (card no#: 04-006-9376). No other phase was found in the pattern except rhombohedral b-TCP of R3c space group 24 and a similar type of b-TCP has been reported in the literature. 20,25 ) very small peaks (relative intensity ∼1%) out of total 46 peaks were not coincided with the mentioned standard.…”
Section: Characterizationsupporting
confidence: 81%
“…This may result in a decrease in the lattice parameter c and stabilization of the βTCP structure. The existence of silver in Ca(4) positions in Ag-doped βTCP was recently confirmed via the high-angle annular dark-field scanning transmission electron microcopy observations [ 34 ].…”
Section: Resultsmentioning
confidence: 95%
“…Incorporating silver into 𝛽-TCP ceramics has been investigated in several studies. The research by Gokcekaya et al [129][130][131] showed that Ag incorporation into 𝛽-TCP (Ag-𝛽-TCP) can lower the lattice parameters of 𝛽-TCP and suppress the phase-change from 𝛽-TCP to 𝛼-TCP, giving better sintering density and good mechanical strength of 𝛽-TCP. Additionally, it is found that Ag-TCP is characterized by excellent properties such as high silver solubility, good antibacterial properties, and high bioresorbability.…”
Section: Solid-state Reactionmentioning
confidence: 99%